Contextual Inquiry Model to Improve Students’ Science Process Skill on Microbiology Lesson - Hasruddin; Fauziyah Harahap; Mahmud (JPP (Jurnal Pendidikan dan Pembelajaran), 2018)
This study aims to develop the design of contextual inquiry learning model to improve students’ science process skills in microbiology lectures. The design of learning model developed in the form of contextual inquiry learning model. This Research and Development covers three stages of research that are: Needs analysis, Development of contextual inquiry learning model, and Trial of learning design. The research instruments used to collect data consisted of validation sheets by material experts, designers, and linguists, and a description test to measure the skills of the science process. It used descriptive statistics for data analysis. A preliminary study conducted on 40 students attending microbiology lesson indicated the need for microbiology teaching design which applies active learning process based on contextual inquiry. The results of a limited trial of 34 experimental class students and 35 control class students found that the research hypothesis was accepted, which means that contextual inquiry learning model of microbiology enhances students’ process skills higher than conventional method.